2018
DOI: 10.1039/c7cp07821h
|View full text |Cite
|
Sign up to set email alerts
|

Impact of screw and edge dislocations on the thermal conductivity of individual nanowires and bulk GaN: a molecular dynamics study

Abstract: We report the thermal transport properties of wurtzite GaN in the presence of dislocations using molecular dynamics simulations. A variety of isolated dislocations in a nanowire configuration are analyzed and found to considerably reduce the thermal conductivity while impacting its temperature dependence in a different manner. Isolated screw dislocations reduce the thermal conductivity by a factor of two, while the influence of edge dislocations is less pronounced. The relative reduction of thermal conductivit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 73 publications
1
26
2
Order By: Relevance
“…This means that the surface to volume ratio has little effect on c-Si NIs in a-Si matrix. This lack of impact of the surface to volume ratio contrasts with the results obtained for GaN NIs in SiO 2 [ 60 ]. The origin of this difference may be found in the impedance mismatch between GaN and SiO 2 .…”
Section: Resultscontrasting
confidence: 90%
“…This means that the surface to volume ratio has little effect on c-Si NIs in a-Si matrix. This lack of impact of the surface to volume ratio contrasts with the results obtained for GaN NIs in SiO 2 [ 60 ]. The origin of this difference may be found in the impedance mismatch between GaN and SiO 2 .…”
Section: Resultscontrasting
confidence: 90%
“…We note that the overall very high dislocation density of our samples (~10 10 cm -2 ) is insufficient to diminish the intrinsic thermal conductivity of InN appreciably, indicating that phonon-dislocation scattering is weaker than the intrinsic phonon-phonon scattering with this dislocation density. This observation agrees with a recent molecular dynamics calculation 34 , which predicts that an apparent thermal resistance due to dislocations at room temperature can only be observed in GaN when the dislocation density is at least 10 12 cm -2 . For Λ ⊥ , we do not observe any noticeable change as a function of the dislocation density even at 80 K, suggesting that phonons are not strongly scattered along the dislocation lines.…”
Section: Msupporting
confidence: 92%
“…For thermal transport, SD was identified to be a source of anharmonic phonon-phonon scattering and reduces the relaxation time of longitudinal acoustic phonons [6]. Termentzidis et al [12] studied the impact of SDs on the thermal conductivity of individual nanowires and bulk GaN, and found that the interaction between phonons and the core of dislocations and their strain field leads to the decrease of the thermal conductivity. Very recently, Sun et al [1] measured anisotropic heat transport in single-crystal indium nitride films, which is induced by the oriented edge-type and screw-type dislocations.…”
Section: Introductionmentioning
confidence: 99%